Maffucci syndrome: Anaesthetic management and review of literature - Singh, Gyaninder P; Bindu, Barkha; Pandia, Mihir P; Bithal, Parmod K (Journal of Neuroanaesthesiology and Critical Care, 2015)
Maffucci syndrome is a rare, nonhereditary disorder manifesting early in life. The syndrome is characterized by presence of multiple hemangiomas and enchondromas mostly affecting the extremities. Haemangiomas are usually cutaneous, but may sometimes be visceral as well. Enchondromas commonly affect the long bones of the extremities. However, other areas including skull, ribs, vertebrae, larynx and trachea may also be involved. The presence of these lesions in the trachea and/or oropharynx may compromise the airway and cause difficulty during tracheal intubation. Complete airway examination and investigation is important to rule out any such lesion in a patient of Maffucci syndrome before planning for general anaesthesia with tracheal intubation.
Keywords: Enchondromas; haemangiomas; Maffucci syndrome; tracheal intubation